Escrituras de la sombra: la fotografía como gesto - Bertúa, Paula (2020)
In “La fotografía: copia, archivo, firma”, Jacques Derrida affirms that if the problem of reference and truth in photography were to be carefully considered, photography would cease to be a verification of an external, pre-existing entity, to become a purely performative image-production, which in turn entails the multiple, the divisible, the impure. This performative aspect of photography is indeed closer to gesture than to acting or manufacture. Photography qua materiality paradoxically claims a purely mediatic existence, endlessly mediating, and allowing the gesture itself to become visible, as res gesta, that simultaneously supports and exhibits the different physical and chemical elements, procedures, shapes, sizes and colors that inform photographic matter. This is the framework that allows me to analyze Argentine photographers Eduardo Gil, Martín Weber and Gabriel Valansi whose work explores the threshold between the actuality of the present and its referential impossibility. A series of photographic objects, whose becoming, captures in a single gesture a moment and its loss.